Morphology and growth of the Massospondylus braincase (Dinosauria Prosauropoda) - Gow, Chris E (Bernard Price Institute for Palaeontological Research, 1990)
The almost complete disarticulated braincase of a young Massospondylus, and the partial braincase of a very large individual in which the laterosphenoid bones are preserved, are described.
Keywords: Ontogeny; sauropodomorpha